Impact and Implications of Recent and Potential Changes to Brazil's Subnational Fiscal Framework - World Bank (Washington, DC, 2014)
Brazil's subnational fiscal framework has remained a source of unabated controversy despite its relative stability over the past decade. The objective of this study is to evaluate the nature and impact of recent and expected changes to Brazil's subnational fiscal framework in light of these debates. More specifically, this work has focused on recent and proposed changes to: 1) the Tax on Goods Circulation, Communication and Inter-municipal and Inter-state Transportation Services (ICMS); 2) the State Participation Fund (FPE) as well as the transfers from oil and mining royalties; and 3) the subnational debt and borrowing framework. These three broad areas are precisely the ones that are the center of the current debate on Brazil's subnational fiscal framework. In order to achieve the proposed objective, three background papers were commissioned, each covering one of the issues outlined above. The main value-added of this study is an examination-and an attempt at a quantification of the impacts of the changes underway in these three dimensions of Brazil's intergovernmental fiscal framework. The remainder of this synthesis report is organized as follows. Section two provides a brief overview of how Brazil's subnational fiscal framework currently works. Section three describes the ongoing efforts to reform Brazil's subnational fiscal framework and points to the advantages of a more coordinated approach over a piecemeal one. Section four discusses the expected fiscal impact on subnational governments of the most likely reform scenarios. Section five concludes. Finally, the amended proposal also kept the original provisions regarding the validation of past tax incentives unchanged. It included a mandate for past tax incentives to be approved by state legislative and to be disclosed at the official Gazette. The main change was the creation of a provision to safeguard the existing tax incentives until their expiration or 2033, whichever comes first.